2023
DOI: 10.30997/jvs.v9i2.11241
|View full text |Cite
|
Sign up to set email alerts
|

EXPLORE THE IMPORTANCE OF CREATIVITY AND INNOVATION IN MICRO, SMALL AND MEDIUM ENTERPRISES (MSMEs)

Awa Awa,
Palahudin

Abstract: Indonesia is a country with a large number of micro, small and medium enterprises (MSMEs) sectors. MSMEs must apply creativity and innovation in order to face increasingly competitive levels of business competition. Understanding and awareness of the importance of creativity and innovation among MSMEs is still low. Understanding the differences between creativity and innovation is still felt to be ambiguous and wrong. The application of the concepts of creativity and innovation is still considered unimportant,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…In relation to this study, several recent reviews link creativity and product innovation to business continuity (e.g. Anderson et al, 2014;Awa & Palahudin, 2023;da Silva Marinho et al, 2016;Handayani et al, 2022;Li et al, 2022). Although a positive effect was found between creativity and product innovation in increasing business continuity, some exploration results also concluded that creativity and innovation actually had negative implications for business continuity.…”
Section: Business Continuitymentioning
confidence: 68%
“…In relation to this study, several recent reviews link creativity and product innovation to business continuity (e.g. Anderson et al, 2014;Awa & Palahudin, 2023;da Silva Marinho et al, 2016;Handayani et al, 2022;Li et al, 2022). Although a positive effect was found between creativity and product innovation in increasing business continuity, some exploration results also concluded that creativity and innovation actually had negative implications for business continuity.…”
Section: Business Continuitymentioning
confidence: 68%
“…In educational settings, fostering students' creative thinking becomes essential, particularly in subjects like chemistry, which enhances the ability to interpret representations [8]. Additionally, creativity enables students to use their imagination for problem-solving, applying innovative and inventive approaches [9], [10].…”
Section: Localmentioning
confidence: 99%